A Numerical Study on Predicting Bond-Slip Relationship of Reinforced Concrete using Surface Based Cohesive Behavior (Fracture and Structural Integrity, 2024)
Overall structural integrity and load transfer between concrete and reinforcement enabling composite action relies on the bond between concrete and reinforcement. Bond strength determination of reinforced concrete is an essential task that a pullout test can determine. Experimental pullout behaviour can be affected by various parameters, such as concrete and steel strength, boundary conditions, etc. Therefore, a parametric study on pullout tests is time-consuming. In addition, measurements of internal stress-strain components and damages of constitutive materials are also difficult in experimental endeavours. In this context, finite element (FE) models should be developed to perform a parametric study with cost and time-saving. This study proposes a finite element modeling strategy of reinforced concrete under pullout force by using the expected failure mechanism to predict bond-slip behaviour in ABAQUS. In FE models, surface-to-surface cohesive interaction behaviour was used to assign interaction between reinforcement and concrete. The proposed modelling strategy was validated with available experimental data from four reference specimens, having all possible failures (i.e., pullout, splitting, and splitting-pullout) under pullout loading. The finite element analysis showed that the proposed FE modeling strategy performed well in predicting bond-slip behaviour in elastic regions. Additionally, maximum bond stresses were predicted satisfactorily, except for the splitting failure pattern, using the proposed FE modelling strategy.
Keywords: Bond-slip model; Pullout test; Surface-to-surface cohesive behavior; FEM; Bond stress-slip curve